STUDI PENGGUNAAN ANTIBIOTIK EMPIRIS DAN DEFINITIF PADA PASIEN BEDAH DI RUANG KANA RSUP Dr. HASAN SADIKIN BANDUNG - Nurgraini Fauziyyah, Meita
Antibiotics are drugs that are used to prevent and treat bacterial infections. Antibiotics for therapy can be empirical, that is in cases where the bacteria that causes the infection is unknown, or definitive, that is in cases where the bacteria that causes the infection and the bacterial resistance patterns are known. This study was conducted to evaluate the use of empirical and definitive antibiotics based on indications, correction in leukocyte counts, antibiotic sensitivity, dosage, and duration of antibiotic use, and to identify the correlation between the use of empirical and definitive antibiotics to the therapy outcome of surgical patients in the Kana Ward of Dr. Hasan Sadikin Hospital in January-June 2018. This study used a descriptive, cross-sectional and non-parametric analysis in a retrospective method from medical records with purposive sampling technique. The results showed that the used of empirical antibiotics were 93.10% and the most commonly used antibiotics were intravenous ceftriaxone (60.80%). From the 43 results of bacterial culture examination, 62.79% were sensitive and 37.21% were resistant to antibiotics, with all bacteria were sensitive to amikacin and ciprofloxacin, and all bacteria were resistant to ampicillin-sulbactam. Based on indications and correction in the leukocyte counts, there were 27.51% inappropriate use of empirical antibiotics, and based on antibiotic sensitivity, there were 41.94% inappropriate use of definitive antibiotics. The inaccuracy of antibiotic doses occured due to subdosage (4.23%), and the inaccuracy duration of use in empirical antibiotics were 2.66% while in definitive antibiotics were 45.16%. Statistically, there was no correlation between the use of empirical and definitive antibiotics (p = 0.718) to the therapy outcome of surgical patients.